2022
DOI: 10.1002/ece3.8628
|View full text |Cite
|
Sign up to set email alerts
|

Identifying core habitats and corridors for giant pandas by combining multiscale random forest and connectivity analysis

Abstract: Habitat loss and fragmentation are widely acknowledged as the main driver of the decline of giant panda populations. The Chinese government has made great efforts to protect this charming species and has made remarkable achievements, such as population growth and habitat expansion. However, habitat fragmentation has not been reversed. Protecting giant pandas in a large spatial extent needs to identify core habitat patches and corridors connecting them. This study used an equal‐sampling multiscale random forest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 118 publications
(166 reference statements)
1
2
0
Order By: Relevance
“…It also increased the likelihood of a continued increase in the population. The results complement previous studies demonstrating that ecological corridors are highly connected, link different patches and increase species movement between patches [70,71]. This suggests that conservationists should focus on connectivity between patches so that biodiversity continues to function [72].…”
Section: Discussionsupporting
confidence: 87%
“…It also increased the likelihood of a continued increase in the population. The results complement previous studies demonstrating that ecological corridors are highly connected, link different patches and increase species movement between patches [70,71]. This suggests that conservationists should focus on connectivity between patches so that biodiversity continues to function [72].…”
Section: Discussionsupporting
confidence: 87%
“…Although human disturbance did not emerge as a prominent factor in our results, it should certainly not be overlooked. Without factoring in climate change, other research has underscored the significance of anthropogenic disturbance in the Liangshan Mountains (Li et al, 2019), other mountain (Sun et al, 2022), and even in future projections (Zhigang et al, 2023). Our result might not have highlighted anthropogenic disturbance as a critical factor, likely due to China's conservation efforts, which encompass the prohibition of commercial logging in 1999 and the launch of two major programs—the Natural Forest Conservation Program and the Grain‐to‐Green Program (Li et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, studies have been conducted to predict the potential distribution of snails in China; however, large-scale predictions are no longer sufficient to meet the requirements for fine control of snails at this stage [ 14 , 15 ]. Studies have shown that factors influencing species distribution may vary at different scales, leading to differences in distribution ranges and even producing opposite conclusions [ 16 , 17 ]. In addition, there are three types of schistosomiasis-endemic areas in China according to the geographical environment and the epidemiological pattern of schistosomiasis: (1) marshland and lake regions, (2) mountainous and hilly regions, and (3) water network regions [ 18 ].…”
Section: Introductionmentioning
confidence: 99%